Evaluation of Dental Caries Prevalence among Children in Mosul City Center Using Significant Caries Index - Saher S Gasgoos; Ghada D Al-Sayagh; Karam H Jazrawi (University of Mosul, College of Dentistry, 2012)
Aims of the study: To evaluate the prevalence of dental caries among children aged 9-10 years in Mo-sul City Center and to compare between traditional index and significant caries index of these students. Materials and Methods: The study sample was obtained from third and fourth class students from eight randomly selected primary schools in Mosul City Center. Sample size was 363 students, 225 fe-males and 138 males. Students' ages were 9 and 10 years. All primary and permanent teeth were ex-amined for the presence of decay, missing or filling teeth/surfaces. Mean DMFT, DMFS, dmft and dmfs were calculated for the students together and separately for each sex. The mean Significant Caries Index (SiC) was also calculated as the mean DMFT and DMFS of the one third of the students with the highest caries scores. Results: The SiC index was significantly higher in all comparisons with tradi-tional DMF index (p < 0.000). A comparison between the two indices indicated that there is a large children subgroup presented with a high caries rate. Conclusions: The mean DMF values did not accu-rately reflect the skewed distribution of dental caries leading to incorrect conclusions that the caries rate of the statewide population is under control. It is better to use SiC index instead of the traditional index.